HUBUNGAN SIKAP IBU DAN DUKUNGAN KELUARGA DENGAN KELENGKAPAN IMUNISASI LANJUTAN PADA BATITA DI PUSKESMAS CURUG TAHUN 2017 - Eka Mardiana Afrilia; Atika Fitriani (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
In 2010 measles was reported in 17,139 cases with an incidence rate of 0.73 per 10,000 population, with the number of cases of measles outbreaks of 2,570 cases in which 6 cases died from measles. Increasing outbreaks of measles in Indonesia, further immunization (booster) needs to be given. The purpose of this research is to know the relationship of mother attitude and family support with completeness of continuation of immunization at toddler at community Health centers Curug year 2017. In this research use descriptive analytic research design with approach of Cross Sectional, sampling is done by technique of Convenience Sampling (Sampling Accidental) By identifying through questionnaires to mothers with toddlers within the work area of the community Health centers observed and measured at the same time, the sample of this study has been determined on the basis of sampling, and the variables of this study have been determined that the dependent variable (completeness of advanced immunization (Booster) on toddlers) and independent variables (mother attitude, and family support). The data obtained in this study were processed by using chi-square test with degree of significance (α = 0,05) with value of ρ value obtained that is (mother attitude (ρ value = 0,001), family support (ρ value = 0,000) = ρ Value <0.05). From bivariat analysis, it is found that there is a significant correlation between mother attitude and family support with completeness of continuous immunization (booster) at toddler at community Health centers Curug year 2017. Suggestion from this research is expected to more health worker to increase promotion and preventive effort to continuity immunization program at Toddlers and increasing cooperation with ranks of village government and health cadres to jointly play an active role in disseminating health information to mothers especially on advanced immunization program.Keywords: immunization, continued (booster), mother attitude, family support